KARAKTERISTIK ANAK AUTISME DI SKHN 01 KOTA CILEGON - Alpiyah Alpiyah; Yahdinil Firda Nadhirah (STKIP Subang, 2024)
This research aims to describe the characteristics of children on the autism spectrum at SKHN 01 Cilegon City, including aspects of communication, social interaction, repetitive behavior and sensory needs. This research uses a qualitative descriptive approach with observation methods, interviews with teachers and parents, and documentation analysis. The research results show that children with autism at SKHN 01 have a variety of unique characteristics. Children show difficulties in verbal and nonverbal communication, while others have limited social interaction patterns. Repetitive behaviors, such as tapping the table or thigh, often appear as a form of sensory need or mechanism to manage emotions. The school supports children through an individual approach, including the use of visual aids, structured timetables